Proceedings of the fourth Resilience Engineering Symposium - Erik Hollnagel, Éric Rigaud, Denis Besnard (dir.) (Presses des Mines, 2011)
These proceedings document the various presentations at the Fourth Resilience Engineering Symposium held on June 8-10, 2011, in Sophia-Antipolis, France. The Symposium gathered participants from five continents and provided them with a forum to exchange experiences and problems, and to learn about Resilience Engineering from the latest scientific achievements to recent practical applications. The First Resilience Engineering Symposium was held in Söderköping, Sweden, on October 25-29 2004. Th...